In the eyes of men: Analysis of men first impression formation on Tinder - Gerson Ralph Manuel Kho (Bricolage : Jurnal Magister Ilmu Komunikasi, 2022)
Do not judge the book by its cover. As good as it may sound, it is almost impossible to do so. As inquisitive human nature, we judge people based on what we see on them; the first time we meet them. Even though we did that many times and every time we meet someone new, the research in the field of first impression is little in numbers if we are about to compare within the field of communication science. On top of that, with the development of communication technology, people are seeking someone new as a potential life partner through virtual space. This research employed a qualitative approach to seeking the answer about "how men form a first impression based on a still photograph?". The data in the form of an interview, analyzed using four fundamental concepts of communication: verbal cues, non-verbal cues, information gathering and formation, and lastly, the concept of culture. The result shows that there are several aspects that men emphasize on to make the first impression through a photograph. 1. Facial Features, 2. Existence of makeup, 3. Accessories, 4. Body proportion. Furthermore, specific facial features such as eyes, lips, etc. They are proven to be the most important factor that men use to judge. Cultural values are used as a means of interpretation of the information they could get.